2020
DOI: 10.5089/9781513550251.001
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effects of COVID-19 Containment Measures

Abstract: Containment measures are crucial to halt the spread of the 2019 COVID-19 pandemic but entail large short-term economic costs. This paper tries to quantify these effects using daily global data on real-time containment measures and indicators of economic activity such as Nitrogen Dioxide (NO2) emissions, flights, energy consumption, maritime trade, and mobility indices. Results suggest that containment measures have had, on average, a very large impact on economic activity—equivalent to a loss of about 15 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 11 publications
7
92
0
1
Order By: Relevance
“…Preliminary estimates from the UK Office for National Statistics showed a slightly more than 20% fall in GDP in April 2020, the first full month after the lockdown. Bonadio et al (2020) 45 put the impact on output and incomes (ie GDP) of policies to counter the spread of the infection on GDP averaged across 64 countries even higher, at around 30%. Costs which will come further down the road because of disruption to healthcare 46 and education are harder again 47 to measure relative to the more immediate effects on economic production and employment 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary estimates from the UK Office for National Statistics showed a slightly more than 20% fall in GDP in April 2020, the first full month after the lockdown. Bonadio et al (2020) 45 put the impact on output and incomes (ie GDP) of policies to counter the spread of the infection on GDP averaged across 64 countries even higher, at around 30%. Costs which will come further down the road because of disruption to healthcare 46 and education are harder again 47 to measure relative to the more immediate effects on economic production and employment 48 …”
Section: Discussionmentioning
confidence: 99%
“…Linking the total population by age group with employment 49 and COVID‐19 Age‐specific Mortality rate 50 by age group shows that only 7% of those that have died may have been in employment. Coronavirus (COVID‐19) Community Infection Survey 51 showed that the infection rate amongst employed age group 20‐48 was 70% higher than the stay at home age groups, and combining this with the population by age group shows 51% of all infections and 1% of deaths were recorded within this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to limit the spread of the pandemic, the governments of countries decided to confine millions of people to their homes, which turned out to be an effective way to slow down the increase in new infections, but it brought significant economic costs, such as the collapse of many enterprises or the depletion of a large part of societies destitute. Research has shown that short-term economic losses were greater in countries with fewer fiscal stimuli and with more limited use of monetary policy tools (Deb et al, 2020). In the corporate sector, small enterprises are in the most difficult situation, due to their limited cash resources, they have little chance of waiting out the hard time of the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A great deal of evidence is already emerging on the (narrow) economic impacts of restrictions. Estimates made by Deb et al (2020) to identify the particular effect of restrictive policies (lockdown) suggest that they reduced economic activity by 15 per cent in the 30 days after they were adopted. They find that stay-at-home requirements and workplace closures are the costliest in economic terms.…”
Section: The Costs Of Lockdownsmentioning
confidence: 99%